Pengembangan Media Ular Tangga Berbasis Kontekstual Materi Melihat Karena Cahaya Mendengar Karena Bunyi Kelas V Sekolah Dasar - Eva Yolandha Fachrunnisya; Mimin Ninawati (Universitas Negeri Padang, 2025)
This study focuses on the Development and feasibility testing of a contextual-based visual Snakes and Ladders learning media for teaching Integrated Science (IPAS), specifically the topics